Preparation and Properties of Stearic Acid/Nanocellulose Composite Phase Change Energy Storage Materials - Yufeng ZHAO; Yanghua CHEN (Medžiagotyra, 2024)
To solve the problems of liquid phase leakage and poor thermal conductivity of organic phase change energy storage materials, a novel composite phase change energy storage material (SA/CNF) based on stearic acid (SA) and nanocellulose (CNF) was prepared in this study and added graphene to enhance its thermal conductivity. For the prepared composite phase change materials (SFs) with different ratios, shape stability, and testing experiments showed that the maximum adsorption rate of CNF on SA reached 80 %. The properties of SA/CNF were then characterized by various instruments. The results show that SA and CNF are compounded together by physical interaction. More than 93 % of SA in the composite phase change energy storage material SA/CNF is able to store and release heat through the phase change process, and the latent heat of phase change of pure SA is 206.3 J/g, while the latent heat of phase change of the composite phase change material SA/CNF with 20 % of CNF is 156.2 J/g, and they both have good cycling stability. The addition of graphene enhances the thermal conductivity of SA/CNF to a large extent, and the thermal conductivity at a graphene ratio of 5 % is 261 % higher than that of SA/CNF without graphene. SA/CNF is an environmentally friendly energy storage material with very high application prospects.